Visual Identity Flowdys Thrift - Dicki Akdhan Chrisnawan (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Flowdys Thrift is a clothing shop owned by Bunga Rahmadillah which was founded in mid-2021. It operates in the field of fashion or used clothing that is suitable for use. Located on Jalan Pasir Parupuk Tabing Simp. Gia no 17 Kec. Koto Tangah, Padang City, West Sumatra. However, the basic problem with Flowdys Thrift is that it is faced with many competitors who are old and new who will be involved in the same business field. The aim of designing a visual identity is to design a logo by applying good design principles, so that it will produce a logo that is unique, simple and easy to remember in order to form a consistent identity, increase business aspiration, as well as differentiate it from other competitors so that it is more easily recognized and remembered by the public. consumer The visual identity design method used is the Glass box method, starting from data collection, interviews and observations so that problems that occur can be identified, which will later be analyzed using SWOT theory, resulting in a Manual Book as the main media containing concepts, gird systems, colors, typography, and supporting media such as posters, stickers, T-shirts, tumblers/thermos, lanyards, stamps.